1996
DOI: 10.1007/bf02445194
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the effects of dimebon, obsidan, finoptin, and cordaron on the functional state of ischemic focus and size of necrotic zone in experimental myocardial infarction

Abstract: Dimebon, an antihistamine agent, exerts a moderate antianginal effect, improving the function of ischemic focus in the myocardium and decreasing the necrotic zone in experimental myocardial infarction. Dimebon is less active than obsidan, finoptin (except for the size of the necrotic zone), and cordaron. Key Words: dimebon; obsidan; .finoptin; cordaron; ischemia; myocardial infarction; treatmentThe Hx-receptor blocker dimebon exhibits antiarrhythmic activity in a wide dose range (0.1-10.8 mg/kg), being effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Based on the results of these studies, Dimebon was classified as a low toxic substance. A pronounced antiarrhythmic effect of Dimebon and its beneficial effect in certain heart conditions have also been emphasized 21–23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of these studies, Dimebon was classified as a low toxic substance. A pronounced antiarrhythmic effect of Dimebon and its beneficial effect in certain heart conditions have also been emphasized 21–23…”
Section: Discussionmentioning
confidence: 99%
“…A pronounced antiarrhythmic effect of Dimebon and its beneficial effect in certain heart conditions have also been emphasized. [21][22][23] In summary, Dimebon has a combination of pharmacological and safety properties that suggest the drug as a candidate for the use in the therapy of Alzheimer's disease. The results of the study reported here show that Dimebon has a great potential as a new medication that may not only improve cognitive functions, but, most importantly, may prevent the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%